Mutant HTT (huntingtin) impairs mitophagy in a cellular model of Huntington disease. Issue 3 (4th March 2021) - Franco-Iborra, Sandra; Plaza-Zabala, Ainhoa; Montpeyo, Marta; Sebastian, David; Vila, Miquel; Martinez-Vicente, Marta
ABSTRACT: The precise degradation of dysfunctional mitochondria by mitophagy is essential for maintaining neuronal homeostasis. HTT (huntingtin) can interact with numerous other proteins and thereby perform multiple biological functions within the cell. In this study, we investigated the role of HTT during mitophagy and analyzed the impact of the expansion of its polyglutamine (polyQ) tract. HTT is involved in different mitophagy steps, promoting the physical proximity of different protein complexes during the initiation of mitophagy and recruiting mitophagy receptors essential for promoting the interaction between damaged mitochondria and the nascent autophagosome. The presence of the polyQ tract in mutant HTT affects the formation of these protein complexes and determines the negative consequences of mutant HTT on mitophagy, leading to the accumulation of damaged mitochondria and an increase in oxidative stress. These outcomes contribute to general mitochondrial dysfunction and neurodegeneration in Huntington disease. Abbreviations : AMPK: AMP-activated protein kinase; ATG13: autophagy related 13; BECN1: beclin 1, autophagy related; BNIP3: BCL2/adenovirus E1B interacting protein 3; BNIP3L/Nix: BCL2/adenovirus E1B interacting protein 3-like; CCCP: carbonyl cyanide 3-chlorophenyl hydrazone; DMEM: Dulbecco's modified eagle medium; EDTA: ethylene-diamine-tetra-acetic acid; EGFP: enhanced green fluorescent protein; EGTA: ethylene glycol bis(2-aminoethyl ether)tetraacetic acid; FUNDC1: FUN14 domain containing 1; HD: Huntington disease; HRP: horseradish peroxidase; HTT: huntingtin; LC3-II: lipidated form of MAP1LC3/LC3; mtDNA: mitochondrial deoxyribonucleic acid; MTDR: MitoTracker Deep Red; MTOR: mechanistic target of rapamycin kinase; MTORC1: mechanistic target of rapamycin kinase complex 1; NBR1: NBR1, autophagy cargo receptor; CALCOCO2/NDP52: calcium binding and coiled-coil domain 2; OCR: oxygen consumption rate; OPTN: optineurin; OXPHOS: oxidative phosphorylation; PIK3C3/VPS34: phosphatidylinositol 3-kinase catalytic subunit type 3; PIK3R4/VPS15: phosphoinositide-3-kinase regulatory subunit 4; PINK1: PTEN induced putative kinase 1; PLA: proximity ligation assay; PMSF: phenylmethylsulfonyl fluoride; polyQ: polyglutamine; PtdIns3K: phosphatidylinositol 3-kinase; ROS: reactive oxygen species; Rot: rotenone; SDS-PAGE: sodium dodecyl sulfate-polyacrylamide gel electrophoresis; SEM: standard error of the mean; SQSTM1/p62: sequestosome 1; TMRM: tetramethylrhodamine methyl ester; UB: ubiquitin; ULK1: unc-51 like kinase 1.